Strategi adaptasi Motivational Interviewing (AMI): aspek keyakinan, empati dan pe-rubahan tingkah laku dan kesannya terhadap latihan kaunseling penyalahgunaan dadah - Puteri Hayati Megat Ahmad; Nurul Hudani Md Nawi; Azreel Azim Abdul Alim (Penerbit Universiti Kebangsaan Malaysia, 2019)
Adaptation Motivational Interviewing strategy is a counseling strategy and psychotherapy approach to obtain clients’ motivation during treatment by focusing on a positive change product of the client. The interest in running of such program has increased in reducing cases of drug abuse. Therefore, this study was done to examine the effectiveness of Adapation Mo-tivational Interviewing training toward confidence, empathy and behavioral change aspects among selected prison officers in Sabah. A total of 65 prison officers, 53 males (72.6%) and 12 females (16.4%) with mean age of 32.25 (SD=7.19) participated in the study. The study is a quantitative study that used a quasi-experimental method and questionnaires (Counseling Response Questionnaires, Confidence and Knowledge Scale as well as a developed moduled by the researchers that is consistent with The Behavior Change Counseling Index (BECCI)). Overall the study showed that there was a significant difference in the effect of Adaptation Motivational Inter-viewing training among the prison officers in Sabah between the scores of confidence (t (63) = -11.35, k<.05) and empathy (t (63) = -21.90, k<.05) before and after training. Furthermore, behavioural change aspect before and after training also showed a significant difference (t (63) = -14.67, k<.05). Consequently, this study contributes to the importance of the effort in identifying confidence, empa-thy and behavioral change among the prison officers in Sabah. This drug abuse counseling program can be a guideline to standardize the development and quality of life among prison officers without neglecting the integrity element. Moreover, an improvement has to be identified to increase the effec-tiveness of the program in the series of AMI training in the future.